2012
DOI: 10.1007/s11214-012-9902-4
|View full text |Cite
|
Sign up to set email alerts
|

The ChemCam Instrument Suite on the Mars Science Laboratory (MSL) Rover: Body Unit and Combined System Tests

Abstract: International audienceThe ChemCam instrument suite on the Mars Science Laboratory (MSL) rover Curiosity provides remote compositional information using the first laser-induced breakdown spectrometer (LIBS) on a planetary mission, and provides sample texture and morphology data using a remote micro-imager (RMI). Overall, ChemCam supports MSL with five capabilities: remote classification of rock and soil characteristics; quantitative elemental compositions including light elements like hydrogen and some elements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
265
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 459 publications
(290 citation statements)
references
References 42 publications
8
265
0
2
Order By: Relevance
“…2, panel G). A preliminary LoD around 5-10% was obtained for SO 3 . The detection of S is particularly important for the identication of calcium sulfates.…”
Section: Non-metallic Elements (H C O P S)mentioning
confidence: 93%
See 1 more Smart Citation
“…2, panel G). A preliminary LoD around 5-10% was obtained for SO 3 . The detection of S is particularly important for the identication of calcium sulfates.…”
Section: Non-metallic Elements (H C O P S)mentioning
confidence: 93%
“…10). In the laboratory, prior to launch, Wiens et al 3 reported on experiments at Mars ambient pressure in a ne-grained soil simulant using JDo-1 (73% of this standard has grain sizes <20 mm). The hole produced by the ight instrument was 1.4 mm in diameter aer 50 pulses and 1.8 mm aer 150 pulses.…”
Section: Small Scale and Sample Heterogeneitymentioning
confidence: 99%
“…8; Robinson et al, 2013); 8. observations of landscape geomorphology ( Fig. 9) and airborne dust; 9. imaging of other instrument hardware (e.g., the APXS calibration target, the CheMin inlet funnel, the Sample Analysis at Mars (SAM) tunable laser spectrometer (TLS), the Rover Environmental Monitoring System (REMS) ultraviolet (UV) sensor and the ChemCam remote warm electronics box (RWEB)) to support their safety and health (Blake et al, 2013;Edgett et al, 2012;Gómez-Elvira et al, 2012;Wiens et al, 2012;Campbell et al, 2014;Figs. 10-12); and 10. observations of the properties and configuration of eolian dust that settled on natural and rover hardware surfaces (Fig.…”
Section: Summary Of Mahli Activitiesmentioning
confidence: 99%
“…This is onboard focus merge product 0808MH0001930000300748R00. MAHLI periodically images the ChemCam RWEB window, which contains the instrument's laser, telescopic optics and remote microscopic imager (RMI) (Maurice et al, 2012), to detect changes in dust contamination. MAHLI is also sometimes used to image the fiber optic cable that carries ChemCam signals to the spectrometers within the rover body , to look for cable wear.…”
Section: Use Limitationsmentioning
confidence: 99%
See 1 more Smart Citation